Fusobacterium nucleatum subsp. nucleatum RadD binds Siglec-7 and inhibits NK cell-mediated cancer cell killing - Johanna Galaski; Ahmed Rishiq; Mingdong Liu; Reem Bsoul; Almog Bergson; Renate Lux; Gilad Bachrach; Ofer Mandelboim (2024)
is an oral commensal bacterium that can colonize extraoral tumor entities, such as colorectal cancer and breast cancer. Recent studies revealed its ability to modulate the immune response in the tumor microenvironment (TME), promoting cancer progression and metastasis. Importantly,